Physicochemical properties and capsicinoids content of Thai chili cultivars used in southern sour curry paste (Kaeng Som) - Inprasit, Khanittha; Chookaew, Lalita; Suksawad, Janejira; Chuenwatthana, Sutachaya (Bulletin of Applied Sciences, 2022)
Chili is a spice that is regularly used in food production to enhance the color, taste, and flavor all over the world. The pungency of chili originated from capsaicinoids. Therefore, this research aims to analyzed the physical and chemical properties of Thai chili cultivars used in Southern Kaeng Som. Five cultivars of Thai chilies (8 samples) were collected, including KHO.1P, KHO.2P, KAR.2R, JIN.2K, YOD.1N, YOD.2N, KEN.2R and KEN.2P. In order to find their quality, the physical appearance, physical properties were analyzed. The physical analysis showed that the color of fresh chili samples was found as red to yellow-green. The chemical analysis showed that their the total soluble solid (TSS), pH, total acidity (TA) and maturity index were found in the range of 6.0-13.0 °Brix, 5.09-5.60, 0.11-0.18% and 35.3-86.7, respectively. Moreover, their capsaicinoids were found in the range of 3,048.64- 6,832.56 mg/kg dry weight. The pungency of chili samples was classified to very highly pungent (>80,000 SHU): YOD.1N > KAR.2R > KEN.2P > YOD.2N > KHO.1P, and highly pungent (25,000 - 70,000 SHU): KEN.2R > KHO.2P > JIN.2K, respectively. Furthermore, their capsaicinoids and pungency depended on cultivars, agricultural area, growing conditions, and maturity stage.